2023
DOI: 10.1002/cncr.34780
|View full text |Cite
|
Sign up to set email alerts
|

Entospletinib with decitabine in acute myeloid leukemia with mutant TP53 or complex karyotype: A phase 2 substudy of the Beat AML Master Trial

Abstract: Background: Patients with acute myeloid leukemia (AML) who have tumor protein p53 (TP53) mutations or a complex karyotype have a poor prognosis, and hypomethylating agents are often used. The authors evaluated the efficacy of entospletinib, an oral inhibitor of spleen tyrosine kinase, combined with decitabine in this patient population.Methods: This was a multicenter, open-label, phase 2 substudy of the Beat AML Master Trial (ClinicalTrials.gov identifier NCT03013998) using a Simon two-stage design. Eligible p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…In a randomized phase II study to investigate the addition of bortezomib, a proteasome inhibitor on 10-day decitabine showed a poor response in patients with TP53-mutated AML [69]. A substudy of the Beat AML Master Trial tested the combination of a Syk inhibitor, entospletinib, and 10-day decitabine as a phase II study, which also demonstrated a disappointingly low CR rate of 13.3% and short median OS of 6.5 months [70] (Table 1). However, the addition of venetoclax, a promising novel drug in the field of AML treatment, did not increase the response rate of TP53-mutated AML.…”
Section: Despair and Hope In Tp53-mutated Aml: Is The Future Bright?mentioning
confidence: 99%
“…In a randomized phase II study to investigate the addition of bortezomib, a proteasome inhibitor on 10-day decitabine showed a poor response in patients with TP53-mutated AML [69]. A substudy of the Beat AML Master Trial tested the combination of a Syk inhibitor, entospletinib, and 10-day decitabine as a phase II study, which also demonstrated a disappointingly low CR rate of 13.3% and short median OS of 6.5 months [70] (Table 1). However, the addition of venetoclax, a promising novel drug in the field of AML treatment, did not increase the response rate of TP53-mutated AML.…”
Section: Despair and Hope In Tp53-mutated Aml: Is The Future Bright?mentioning
confidence: 99%
“…Acute myeloid leukemia (AML) is a highly prevalent malignancy of the blood system. , Its mortality rate has steadily increased in recent years . The treatment of AML has seen limited advancements in recent decades, apart from conventional chemotherapy and hematopoietic stem cell transplantation. Furthermore, the residual leukemia cells are difficult to be completely eliminated, and the side effects of conventional therapies are significant .…”
Section: Introductionmentioning
confidence: 99%